A Case Study Of Strategies And Management Of APL; Leading Company In Iranian Pistachios Trade - Validashti, Jahangir (2009)
This study is related to the details of Amin Padidar Limited (APL) in their business strategies and plan to be a market leader. This study analyze the current environment, internally and externally of APL in developing marketing strategies to compete as a major player in the pistachios world trade.